2021
DOI: 10.1111/php.13490
|View full text |Cite
|
Sign up to set email alerts
|

Selected Extracts from High Mountain Plants as Potential Sunscreens with Antioxidant Capacity

Abstract: The photoprotective and antioxidant activities of extracts of six species of plants collected in a high mountain ecosystem at 3150 m.a.s.l. were evaluated. In vitro photoprotection according to UVA‐UVB absorption spectrum, Sun Protection Factor (SPF), UVA Protection Factor (UVAPF), (critical wavelength) λc and UVA/UVB Ratio were assessed. Also, the antioxidant activity was determined using the DPPH radical assay and the inhibition of lipid peroxidation in methyl linoleate (MeLo). Total anthocyanins content (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The SPF values of CO and CE when added alone or in combination were determined and then compared with the blank sample and a hybrid commercial sunscreen. The SPF values of the commercial sunscreen were consistent with those reported by Meji ́a-Giraldo et al 61 Meanwhile, the SPF values of the formulations with the added active ingredient were higher than those of the blank control; the values ranged from 20.22 (F2; Table S7) to 59.35 (F4; Table S7). The assays suggested that CO and CE in combination had higher SPF than CO or CE alone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The SPF values of CO and CE when added alone or in combination were determined and then compared with the blank sample and a hybrid commercial sunscreen. The SPF values of the commercial sunscreen were consistent with those reported by Meji ́a-Giraldo et al 61 Meanwhile, the SPF values of the formulations with the added active ingredient were higher than those of the blank control; the values ranged from 20.22 (F2; Table S7) to 59.35 (F4; Table S7). The assays suggested that CO and CE in combination had higher SPF than CO or CE alone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These include propolis cinnamic acids, tea polyphenols, grape seed proanthocyanidins, milk thistle silymarins, algae MAAs, algae terpenes, lichen polyphenols, lignin, and melanin (reviewed in [255][256][257]). A recent study has also demonstrated a positive correlation between the altitude at which the sun-protective plants grow up and the bio-production of metabolites with both AO and photoprotective properties [258]. Therefore, boosting the AO capacity of skin cells by using exogenous AOs appears to be a valuable strategy for preventing UV-induced skin photodamage and photoaging.…”
Section: Natural-based Antioxidants For Skin Protectionmentioning
confidence: 99%
“…Chromanols and chromenols are collective terms for about 230 structures derived from photosynthetic organisms such as plants, algae, cyanobacteria, fungi, corals, sponges, and tunicates [258]. Vitamin E (vit E) represents the most widely distributed and abundant chromanol in nature.…”
Section: Chromanols and Chromenols As Promising Skin Antiaging And Ph...mentioning
confidence: 99%
See 2 more Smart Citations